TRPV2 channel-based therapies in the cardiovascular field. Molecular underpinnings of clinically relevant therapies. (January 2021) - O'Connor, Brian; Robbins, Nathan; Koch, Sheryl E.; Rubinstein, Jack
Abstract: The transient receptor potential (TRP) ion channel family is composed of twenty-seven channel proteins that are ubiquitously expressed in the human body. The TRPV (vanilloid) subfamily has been a recent target of investigation within the cardiovascular field. TRPV1, which is sensitive to heat as well as vanilloids, is the best characterized TRPV channel and is the namesake for the subfamily that includes six members. Research into the function of TRPV2 has suggested that it plays an important role in cardiovascular function. Over the last twenty years a greater understanding of the differences among the TRPV channels has allowed for more precise experimentation and has opened various translational opportunities. TRPV2 has been found to be a both a mechanosensor and a mediator of calcium handling and has been found to play important roles in healthy and diseased cardiomyocytes. These roles have been translated into clinical studies in patients with muscular dystrophy (both agonism and antagonism) as well as in patients with cardiomyopathy and heart failure with reduced ejection fraction. Its role as a structural protein has also been elucidated, though the clinical significance of this finding has yet to be established. Despite the clinical progress that has been made there is still a need for large, prospective randomized studies with TRPV2 channel agonists and antagonists in order to bring these basic and translational science findings to the bedside.